Giant hyperplastic molluscum contagiosum - Wiederkehr, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Molluscum contagiosum (MC) is a common viral infection of the skin in healthy children. Unfortunately, it may be seen in exuberant form in children and adults with leukemia or other types of immunodeficiency, including the acquired immunodeficiency syndrome. It usually appears as a solitary or small group of papules which are characteristically flesh colored, slightly translucent and umbilicated. We report a case of a 40-year-old AIDS patient with multiple keratotic, papillomatous projections on his anterior neck, some resembling cutaneous horns. A skin biopsy specimen revealed the presence of numerous molluscum bodies.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Complications; Diagnosis; Molluscum Contagiosum; Moluskum kontagiozni; Odrasli; Pridobljena, imunska pomanjkljivost, sindrom